2009
DOI: 10.1007/s10311-009-0249-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of Zn-contaminated soil: Feasibility study on the removal of H2S from hot coal-derived gas

Abstract: In this study, zinc-contaminated soils were chosen as a candidate material for the removal of hydrogen sulfide (H 2 S) from hot coal-derived gas. Laboratory experiments showed that H 2 S was decreased to less than 10 ppm when the zinc-contaminated soils were reacted with H 2 S. The best removal temperature of H 2 S was found to be at 550°C in the operating conditions. In addition to zinc species, free iron oxides in contaminated soils also performed an active species to react with H 2 S and enhanced the sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…For instance, H 2 S from coal derived natural gas has been effectively removed by iron-rich and zinc contaminated soils (Ko, 2008(Ko, , 2011Ko and Hsueh, 2012). Moreover, cow manure compost in biofilter columns has shown considerable potential for H 2 S removal, albeit through oxidation as well as precipitation (Zicari, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, H 2 S from coal derived natural gas has been effectively removed by iron-rich and zinc contaminated soils (Ko, 2008(Ko, , 2011Ko and Hsueh, 2012). Moreover, cow manure compost in biofilter columns has shown considerable potential for H 2 S removal, albeit through oxidation as well as precipitation (Zicari, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Among the investigated metal sorbents, studies have primarily focused on Zn oxide (ZnO) and related modied sorbents because they present numerous advantages, such as a favorable thermodynamic property with sulfur species, they are suitable for use at a wide range of operating temperatures, and can reduce the concentration of sulfur species to less than 10 ppm. [7][8][9] However, the reduction of ZnO and subsequent vaporization of elemental Zn remain a severe problem when the temperature is increased to 650 C. 10,11 More recently, Mn oxides and Mn-based oxides have attracted considerable attention for high temperature desulfurization. [12][13][14] The reactivity of Mn-based oxides is higher than that of ZnO, and Mn-based oxides cannot be easily reduced to elemental Mn during hot coal gas desulfurization.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies shown that the natural soils and contaminated soils have a highly reaction ability with H 2 S and thus be used for many times after regeneration process (Ko, 2008(Ko, , 2011. The iron species is the major active metal to react with H 2 S. Unfortunately, the information of kinetic performance is lack due to instrument limitation.…”
Section: Introductionmentioning
confidence: 99%